Positive Law Islamic Criminal Law in the Implemantation of Execution of Confiscated Item from Corruption Criminal Acts - Farihin Tsani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the concept of legal protection in the storage of confiscated goods or evidence based on Government Regulation Number 27 of 1981 and to examine its conformity with Islamic law as well as its implementation in practice. The research employs a qualitative field research method, in which data are collected directly from relevant institutions such as the police, prosecutor’s office, courts, and the State Confiscated Goods Storage House (Rupbasan). The results indicate a discrepancy between Article 44 paragraph (1) of the Criminal Procedure Code (KUHAP), which mandates that confiscated goods be stored in Rupbasan, and the actual practice where such items are often stored in other institutions. In addition, there is a difference in interpretation with Article 1 point 16 of KUHAP. From the perspective of Islamic law, confiscated goods can be analogized as collateral, while corruption is categorized as jarimah ta’zir, where the determination of punishment is left to the authority of ulil amri or judges. Therefore, harmonization between regulations, practical implementation, and Islamic legal values is necessary to ensure legal certainty and justice.